2019
DOI: 10.1016/j.ebiom.2019.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic nomogram for HIV/AIDS patients who underwent antiretroviral therapy: Data from a China population-based cohort

Abstract: BackgroundAccurate forecast of the death risk is crucial to the administration of people living with HIV/AIDS (PLHIV). We aimed to establish and validate an effective prognosis nomogram in PLHIV receiving antiretroviral therapy (ART).MethodsAll the data were obtained from 2006 to 2018 in the Wenzhou area from China AIDS prevention and control information system. Factors included in the nomogram were determined by univariate and multiple Cox proportional hazard analysis based on the training set. The receiver o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 44 publications
0
39
1
Order By: Relevance
“…Harrell's overall C-statistics is 0.76 (95% CI 0.74-0.77) in the validation cohort, which is much lower than the apparent C-statistics (0.93) and in random split validation (0.95) reported in the Wenzhou model development study [13]. The time-dependent C-statistics decreased from 0.81 to 0.74 from 6 months to 3 years after ART initiation and continued decreasing to 0.48 at 10 years (Fig.…”
Section: Discrimination Performancecontrasting
confidence: 60%
See 2 more Smart Citations
“…Harrell's overall C-statistics is 0.76 (95% CI 0.74-0.77) in the validation cohort, which is much lower than the apparent C-statistics (0.93) and in random split validation (0.95) reported in the Wenzhou model development study [13]. The time-dependent C-statistics decreased from 0.81 to 0.74 from 6 months to 3 years after ART initiation and continued decreasing to 0.48 at 10 years (Fig.…”
Section: Discrimination Performancecontrasting
confidence: 60%
“…Recently, a nested case–control study including 750 PLWHA from Wenzhou, China, developed and comprehensively validated a prognostic model for predicting the HIV-related death of PLWHA receiving ART (herein after uniformly referred to as the Wenzhou model) and first developed a simple and intuitive nomogram to help its application among healthcare providers [ 13 ]. This is the first prognostic model for PLWHA developed in the Western Pacific region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that patients with high baseline CD4 + cell counts who initiated ART after a year had a 9% higher risk of AIDS-related death than those with lower baseline CD4 + cell counts who initiated ART after 90 days but within 1 year. Patients with high CD4 + levels at baseline who missed treatment opportunity would have a worse prognosis than those with lower CD4 + levels at baseline [19,20]. Arguments to delay ART initiation based on the use of a CD4 + cell count threshold include concerns about drug resistance, side effects, and resource allocation [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have shown that the GPR can predict cirrhosis and fibrosis in patients with hepatitis B virus infection ( 3 , 4 ) and is also an independent risk factor for a poor prognosis after hepatectomy for hepatitis B virus (HBV)-related HCC ( 5 ). In fact, compared with a single factor, the combination of several independent factors can substantially improve predictive ability ( 6 ). Although some nomogram models have been formulated to predict the prognosis of HCC patients in the past several years ( 7 , 8 ), unfortunately, no universal and widely recognized applicable nomogram model based on the GPR is available for this purpose.…”
Section: Introductionmentioning
confidence: 99%